HUBUNGAN ORIENTASI TUJUAN PENGUASAAN DAN BERPIKIR POSITIF DENGAN EFIKASI DIRI AKADEMIK DALAM PELAJARAN MATEMATIKA PADA SISWA SMA - Ulfah, Nurul; Listiara, Anita (Faculty of Psychology, Diponegoro University, 2017)
This study aims to determine the relationship between mastery goal orientation and positive thinking with academic self-efficacy in math subjects in high school students. Academic self-efficacy in math subjects is an individual belief in his/her ability to accomplish mathematics tasks. The subjects of this research are 140 students of grade XI and XII SMA Mardisiswa Semarang obtained with cluster random sampling technique. The measuring instruments used in this study are academic self-efficacy scale in mathematics subject (30 items, Î± = .933), goal orientation of mastery scale (34 items, Î± = .923), and positive thinking scale (17 items, Î± =. 873). The data analysis method used in this research is simple regression analysis. The results shows that there is a significant positive correlation between goal orientation mastery and academic self-efficacy in math subject (r = .496; p = .000; p <.05) and there is a significant positive relationship between positive thinking and academic self-efficacy in math subject (r = .345; p = .000; p <.05). Mastery goal orientation contributes effectively to 24.6% for academic self-efficacy in mathematics, and positive thinking contributes effectively up to 11.9% for academic self-efficacy in mathematics.Â Â Â